Problematika Nilai Moral dalam Pendidikan Islam di Era Digital: Studi Kasus di MA Al Islam Jamsaren Surakarta - Muslimah, Ana; Mujiburrahman, Mujiburrahman (TSAQOFAH, 2025)
The digital era has had a significant impact on students' lives, particularly in shaping their morals and character. This study aims to identify moral value issues emerging among students at MA Al-Islam Jamsaren Surakarta and to explore Islamic educational strategies, especially within the Islamic Religious Education (PAI) subject in fostering moral character amid the challenges posed by technology and digital media. Using a descriptive qualitative approach, data were collected through in-depth interviews with three PAI teachers as the primary informants. The findings reveal that the main challenges in students’ moral development include the negative influence of social media, a decline in courteous behavior, and weak responsibility regarding academic tasks and learning ethics. Nevertheless, Islamic education through integrative approaches, the habitual practice of Islamic values, and teacher role modelling has proven to be a relevant and contextual strategy. This study underscores the critical role of PAI teachers not only as educators but also as moral mentors and role models for students in navigating the complexities of the digital age.